The Evolution of Surface Magnetic Fields in Young Solar-type Stars. Issue Volume 10:Issue S314(2015) (November 2015) - Folsom, Colin P.; Petit, Pascal; Bouvier, Jérôme; Morin, Julien; Lèbre, Agnès; Donati, Jean-François
Abstract: Surface rotation rates of young solar-type stars display drastic changes at the end of the pre-main sequence through the early main sequence. This may trigger corresponding changes in the magnetic dynamos operating in these stars, which ought to be observable in their surface magnetic fields. We present here the first results of an observational effort aimed at characterizing the evolution of stellar magnetic fields through this critical phase. We observed stars from open clusters and associations, which range from 20 to 600 Myr, and used Zeeman Doppler Imaging to characterize their complex magnetic fields. We find a clear trend towards weaker magnetic fields for older ages, as well as a tight correlation between magnetic field strength and Rossby number over this age range. Comparing to results for younger T Tauri stars, we observe a very significant change in magnetic strength and geometry, as the radiative core develops during the late pre-main sequence.